PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN ATLET KUMITE PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) KARATE DINAS PEMUDA DAN OLAHRAGA (DISPORA) RIAU - Salsabilah Salsabilah; Agus Sulastio; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to know the effect of shuttle run training (X) on the Agility (Y) of Kumite athletes at the Karate Education and Training Center (PPLP) of Riau Youth and Sports Agency (DISPORA). The method used in this research is an experimental method, with the research design used in this study is